2019
DOI: 10.21547/jss.427357
|View full text |Cite
|
Sign up to set email alerts
|

Post-graduate Thesis on Logistics and Supply Chain in Turkey: A Bibliometric Analysis

Abstract: Turkey's advantageous location connects Europe with Asia and which has seas from all three sides gives a potential for being the world's logistics hub. For these reasons enough attention needs to be given to the improvements in logistics and supply chain in Turkey. The purpose of the study is to reveal how the distribution graduate theses in logistics and supply chain prepared in Turkey according to different criteria from 1993 until today. The data of the research were collected from national thesis center an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
(4 reference statements)
0
4
0
3
Order By: Relevance
“…The quality of life of older people living in nursing homes has been found to be significantly worse than that of those living at home (Göktaş, 2006). A negative relationship has also been found between quality of life and loneliness (Weiner et al, 2010;Vuletić and Stapić, 2013;Faruk et al, 2019;Korkmaz, 2019;Szabo et al, 2019).…”
Section: Relations Among Variables and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of life of older people living in nursing homes has been found to be significantly worse than that of those living at home (Göktaş, 2006). A negative relationship has also been found between quality of life and loneliness (Weiner et al, 2010;Vuletić and Stapić, 2013;Faruk et al, 2019;Korkmaz, 2019;Szabo et al, 2019).…”
Section: Relations Among Variables and Hypothesesmentioning
confidence: 99%
“…Since the isolation measures undertaken to counteract the spread of the pandemic have led to some problems related to the wellbeing and health of older adults (Korkmaz, 2019;Bozkurt et al, 2020;Steinman et al, 2020), fear of COVID-19 may affect their quality of life. 2018) revealed that feelings of loneliness were more intense among older adults with insufficient social interaction (i.e.…”
Section: Relations Among Variables and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan analiz sonucunda; en çok kullanılan anahtar kelimenin kent lojistiği olduğu, en fazla ortak yazarlığa sahip olan araştırmacının Eiichi Taniguchi olduğu, yayın sayısı en yüksek olan ülkenin İtalya, en fazla yayın yapan araştırmacının da Eiichi Taniguchi olduğu, kent lojistiği alanında en fazla yayının 2016 yılında yapıldığı ve yayınların tamamına yakınının İngilizce yazıldığı sonucuna ulaşılmıştır. Korkmaz ve Çetinkaya (2019), Türkiye'de 193-2019 yılları arasında lojistik ve tedarik zinciri alanlarında yapılan lisansüstü tez çalışmalarının bibliyometrik analizini SPSS ve Excel paket yazılımlarını kullanarak yapmış, çalışmasında 525 tezi derecelerine, şehirlere, hazırlandıkları üniversitelere, yıllara, bulundukları enstitüye ve tezlerde kullanılan anahtar kelimelere göre değerlendirilmiştir. Bu sayede Türkiye'de lojistik ve tedarik zinciri alanlarında yazılan tezlerin tarihsel gelişimi incelenmiş, çalışmaların çoğunun 2000 yılı sonrasında yapıldığı, İstanbul Teknik Üniversitesi'nin bu alanda en çok çalışma yapan üniversite olduğu tedarik zinciri alanında yapılan çalışmaların büyük çoğunluğunun yönetime ilişkin olduğu sonucuna ulaşmıştır.…”
Section: Bi̇bli̇yometri̇k Anali̇z Kavrami Ve Li̇teratür Taramasiunclassified
“…Geçmiş yıllarda lojistiğin çeşitli alanları ile ilgili (kent lojistiği, tersine lojistik gibi) bibliyometrik analizler yapılmış olsa da (Charvet vd., 2008;Georgi vd., 2013;Wang vd., 2013;Suvacı, 2016;Hajduk, 2017;Quasier vd., 2017;Erturgut ve Gürler, 2019;Korkmaz ve Çetinkaya, 2019;Savrun ve Mutlu, 2019) afet ve insani yardım lojistiğini konu alan bibliyometrik analizler konusunda literatürde boşluk olduğu; bu konuda yapılan akademik çalışmaların (Zary vd., 2014;Ceballos Parra, 2015;Tisott vd., 2018) yeterli düzeyde olmadığı ve bu konuya yönelik çalışmalara ihtiyaç duyulduğu görülmektedir. Bu bağlamda, bu araştırmanın temel problemi literatürde mevcut olan bu boşluğu doldurmak ve ilgili literatüre katkıda bulunmak olarak belirlenmiştir.…”
Section: Introductionunclassified